Experimental investigation of oil spray cooling in electrical machines with hairpin windings - Liu, Chuan (2020)
Hairpin windings are gaining increasing popularity in recent years due to their ad-vantages in improving electrical machine performance while reducing manufacturing time and costs. Machines adopting hairpin windings can achieve higher torque density and power density while enabling them to be manufactured automatically on a large scale to meet the increasing demand from transport electrification. Their geometrical features introduce new challenges and opportunities for thermal management. In partic-ular, spray cooling is increasingly being used, since hairpin windings open up regular and accurately defined gaps in the end-windings compared to the traditional random wind-ings. This research proposes a reduced dimensionless correlation based on previous empirical models. A simple experimental setup is designed and manufactured to determine the pa-rameters in the correlation using two off-the-shelf hydraulic nozzles. The established correlations are then used to predict the nozzle’s cooling performance, and the results are validated experimentally using an existing stator with hairpin windings. Lumped parameter thermal network modelling is used to evaluate the spray cooling de-sign’s performance based on an existing machine, and the results are compared to those of a conventional water jacket cooling design, demonstrating spray cooling’s superior cooling ability when combined with hairpin windings. Additional experimental results of other types of nozzles and oil-jet cooling are also re-ported to provide design guidelines to machine designers who required to implement such cooling setups in their design.